Molecular Imaging of Inflammation in Inflammatory Bowel Disease with a Clinically Translatable Dual-Selectin–targeted US Contrast Agent: Comparison with FDG PET/CT in a Mouse Model - Wang, Huaijun (Radiological Society of North America, Inc., 2013)
PURPOSE: To develop and test a molecular imaging approach that uses ultrasonography (US) and a clinically translatable dual-targeted (P- and E-selectin) contrast agent (MB(Selectin)) in the quantification of inflammation at the molecular level and to quantitatively correlate selectin-targeted US with fluorodeoxyglucose (FDG) combined positron emission tomography (PET) and computed tomography (CT) in terms of visualization and quantification of different levels of inflammation in a murine acute colitis model. MATERIALS AND METHODS: Animal studies were approved by the Institutional Administrative Panel on Laboratory Animal Care at Stanford University. MB(Selectin) was developed by covalently binding an analog of the naturally occurring binding ligand P-selectin glycoprotein ligand 1 fused to a human fragment crystallizable(or Fc) domain onto the lipid shell of perfluorobutane and nitrogen-containing MBs. Binding specificity of MB(Selectin) was assessed in vitro with a flow chamber assay and in vivo with a chemically induced acute colitis murine model. US signal was quantitatively correlated with FDG uptake at PET/CT and histologic grade. Statistical analysis was performed with the Student t test, analysis of variance, and Pearson correlation analysis. RESULTS: MB(Selectin) showed strong attachment to both human and mouse P- and E-selectin compared with MB(Control) in vitro (P ≤ .002). In vivo, US signal was significantly increased (P < .001) in mice with acute colitis (173.8 arbitrary units [au] ± 134.8 [standard deviation]) compared with control mice (5.0 au ± 4.5). US imaging signal strongly correlated with FDG uptake on PET/CT images (ρ = 0.89, P < .001). Ex vivo analysis enabled confirmation of inflammation in mice with acute colitis and high expression levels of P- and E-selectin in mucosal capillaries (P = .014). CONCLUSION: US with MB(Selectin) specifically enables detection and quantification of inflammation in a murine acute colitis model, leveraging the natural pathway of leukocyte recruitment in inflammatory tissue. US imaging with MB(Selectin) correlates well with FDG uptake at PET/CT imaging. © RSNA, 2013 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.13122509/-/DC1